2015
DOI: 10.1186/s12875-015-0390-y
|View full text |Cite
|
Sign up to set email alerts
|

Perceived determinants of cardiovascular risk management in primary care: disconnections between patient behaviours, practice organisation and healthcare system

Abstract: BackgroundAlthough conditions for high quality cardiovascular risk management in primary care in the Netherlands are favourable, there still remains a gap between practice guideline recommendations and practice. The aim of the current study was to identify determinants of cardiovascular primary care in the Netherlands.MethodsWe performed a qualitative study, using semi-structured interviews with healthcare professionals and patients with established cardiovascular diseases or at high cardiovascular risk. A fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
(30 reference statements)
2
13
0
Order By: Relevance
“…Consistent with the findings from this study, recent research from the Netherlands highlights the gap between positive policy intent and implementation of CVD risk assessment in practice, 21 with patient, organisation and health system factors all influencing implementation in primary care. A systematic review of breast cancer risk prediction models found that the model most widely implemented in practice was the one that was most widely available, rather than the model with the best predictive ability.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with the findings from this study, recent research from the Netherlands highlights the gap between positive policy intent and implementation of CVD risk assessment in practice, 21 with patient, organisation and health system factors all influencing implementation in primary care. A systematic review of breast cancer risk prediction models found that the model most widely implemented in practice was the one that was most widely available, rather than the model with the best predictive ability.…”
Section: Discussionsupporting
confidence: 89%
“…This would be in line with findings from the HYDRA study (Hypertension and Diabetes Risk Screening and Awareness Study), which reported on an insufficient BP control that seemed to be unnoticed by the treating physicians [ 9 ]. Another issue might be the mismatch of insufficient knowledge and compliance from patients´ side and the lack of time for a comprehensive evaluation of all guidelines applying for an individual patient combined with explanations and close guidance from physicians´ side [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A tailored implementation program was developed in a systematic, stepwise process. We have reported on the various steps in this developmental process before [ 6 8 , 12 ]. First, prevailing clinical guidelines [ 13 , 14 ] and clinical audit data were analyzed to define the following interrelated targets for improvement: systolic blood pressure (SBP) <140 mmHg in patients with established CVD or in patients at high risk for CVD; low-density lipoprotein (LDL) cholesterol <2.5 mmol/l in patients with established CVD or in patients at high risk for CVD; promote lifestyle changes in patients with (high risk for) CVD; create a risk profile for patients with chronic kidney disease.…”
Section: Methodsmentioning
confidence: 99%
“…Then, an interview study was done, involving physicians, nurses, and patients, which identified 139 plausibly important determinants of practice (“barriers or enablers of implementation”). Of this list, a set of 11 determinants was selected based on importance and changeability as judged by the research team and used for subsequent steps [ 8 , 12 ]. Subsequently, group interviews with different stakeholders and patients generated 181 suggested strategies for implementation, which were perceived to address the selected set of 11 most relevant determinants [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation